A genome-guided approach to the study of novel secondary metabolites in quarry-derived actinomycetes - Tan, Daryn Fu Ern (Nanyang Technological University, 2019)
The recent revival of microbial natural product discovery is motivated by the discovery of cryptic biosynthetic gene clusters (BGCs) with developments in genome sequencing technology. A genome-guided approach was employed in this study to discover natural products produced by the actinomycetes strain Streptomyces sp. P46 isolated from the Pulau Ubin Quarry. Genome sequencing and mining have revealed at least 33 BGCs, of which 18 were considered to be cryptic. Two methods were concurrently used to activate these cryptic BGCs – altering the fermentation media conditions (i.e., one strain many compounds or OSMAC approach) and overexpressing local regulator genes. A novel compound (named as Tasikamide A) with anticancer activity was isolated and its chemical structure was determined. Tasikamide A is putatively produced by BGC 20, a non-ribosomal peptide synthetase (NRPS)-polyketide synthase (PKS) hybrid cluster. Apart from Tasikamide A, several other potentially novel compounds have also been detected through the OSMAC approach and are in the process of being isolated and characterised. In addition to the OSMAC approach, a genetic method was employed to target novel NRPS-PKS hybrid clusters BGCs 12, 14 and 28 to discover novel natural products. An overexpression plasmid was successfully used to express locally activating regulators to generate two overexpression mutant strains (P46 C12-ACT and P46 C28-ACT). The two mutant strains were sub-cultured in several culture media and the organic extract of the culture broth and biomass were subjected to metabolite profiling. Two compounds (a and b) were consistently produced by P46 C28-ACT and were identified to be of interest due to their unique retention time and UV-Vis spectra. While compound a is likely to be furaquinocin A, a known compound, the identity of compound b remains to be established. Unexpectedly, several compounds produced by the wild type P46 strain were not produced by P46 C12- ACT, suggesting that the overexpressed regulator could have been a repressor. Overall, my studies demonstrated that P46 is a biosynthetically talented Streptomyces strain in producing novel natural products and set the stage for the activation of cryptic BGCs using the genetic tools validated in this study.